The Influence of Entrepreneurship Education and Entrepreneurial Spirit on Entrepreneurial Interest - Aliman Wiranta; Aghni Aulia Aziz (Medikun Publisher, 2024)
Entrepreneuship is an important force in a country's economy. Fostering an entrepreneurial spirit is believed to be a solution in reducing unemployment. This research aims to explain the effect of entrepreneurship education on the entrepreneurial spirit mediated by entrepreneurial interest in students of class XII SMKS Bina Nasional Informatika, consisting of majors in Network Computer Engineering, Office Administration, and Accounting. The number of respondents taken amounted to 100 respondents using the Slovin formula and probability sampling techniques. The data has been collected and processed using path analysis techniques. This study shows that each variable tested has been valid and reliable, and is feasible in the model according to the path analysis test so that this research can be done. The results of the analysis prove that the variables of entrepreneurship education and entrepreneurial spirit have a significant positive effect on entrepreneurial interest.